Bridging the information gaps on livestock market through information communication technology (ICT) in Ethiopia - Alemayehu, Sintayehu; Tesfaye, Lidya; Regassa, Alemayehu; Schrier, Jason; Girvetz, Evan Hartunian (2021)
Although with the largest livestock population in Africa, Ethiopia has not benefited from its livestock a resource to the scale that is expected due to several factors. The lack of a well-established market information system, which provides timely and reliable information across the primary and secondary markets is one of the main challenges facing the livestock sector in Ethiopia. The use of information communication technology (ICT) is important and plays a critical role in bridging the information gaps on the livestock marketing and early warning-related information to monitor the situation in the value chains. It also creates enabling environment to collect the market data in such a large country in cost-effective ways and reduce paper workloads for the government enumerators. Furthermore, the use of short message service (SMS), web-portal, etc., increases the information dissemination to the stakeholders(pastoralists, traders, government, and non-government) in near real-time to support the decision-making.